THE ROLE OF JOB STRESS IN MEDIATING THE INFLUENCE OF WORK-FAMILY CONFLICTS ON JOB SATISFACTION IN WOMEN EMPLOYEES - Diah Indira Maha Putri; Desak Ketut Sintaasih (Universitas Warmadewa, 2018)
Job satisfaction is a state of one's work reflected by the emotional attitude expressed through one's work attitude. Women careers tend to experience stress than men, especially those who work as nurses and midwives, because the demands of a woman's responsibilities in the family is large enough. This will certainly affect the job satisfaction of a career woman. This study aims to analyze the role of work stress mediation on the influence of work-family conflict on job satisfaction. This study was conducted on health workers (midwives and nurses) women Prima Medika Hospital. The sample of this research is as many as 45 respondents with sample determination method which refers to Roscoe approach (1975). Data collection was done by distributing questionnaires using Likert scale. The analysis technique used is path analysis. Based on the results of the analysis, this study shows the work-family conflict has a positive and significant effect on job stress, job stress has a negative and significant effect on job satisfaction, work-family conflict has a negative and significant impact on job satisfaction. and work stress mediates the influence of work- on job satisfaction.